Deprescribing benzodiazepines: Do Brazilian package inserts address this issue? - Marlon Silva Tinoco; Marcela Oliveira Baldoni; Ériks Oliveira Silva; Amanda Maria de Paiva; Paula Resende Daher Chaves; Mariana Linhares Pereira; Farah Maria Drumond Chequer; André Oliveira Baldoni (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To analyze the presence and quality of content on drug deprescribing in Brazilian package inserts for benzodiazepine drugs. METHODS: Documentary study where we analyzed data on deprescribing extracted from electronic package inserts of drugs containing benzodiazepines; these documents were available at the Brazilian Health Surveillance Agency website. Our search was performed independently by 2 researchers who used the following keywords: "deprescription," "withdrawal," and "tapering." The deprescribing plan, when presented by the package insert, was compared to deprescribing protocols for benzodiazepines found in the literature. Moreover, we assessed the presence of guidance on the maximum length of treatment and risks of long-term use. RESULTS: We found 12 package inserts for benzodiazepines and 100% of them suggested gradual withdrawal; only 1 (8.33%) suggested a systematized deprescribing plan. One document (8.33%) did not offer guidance on maximum treatment duration. Eleven (91.67%) had the information on long-term use possibly causing dependence or tolerance, and 1 (8.33%) did not describe the risks of continuous use. CONCLUSIONS: It is known that benzodiazepines should be withdrawn in a gradual and schematized manner, but package inserts do not currently bring this information in detail. It is of utmost importance that health professionals be educated on their conduct, hence the necessity for updating medication package inserts.